Cultivating the liberally educated mind through a signature program. Issue 1 (2nd January 2017) - Chamlee-Wright, Emily; Hall, Joshua C.; Grube, Laura E.
ABSTRACT: In this article, the authors describe the Miller Upton Programs launched by the Beloit College Department of Economics in 2008. The programs aim to advance student understanding of the nature and causes of wealth and well-being. After describing the programs' core elements, the authors discuss ways in which they leverage economic discourse as a means to advance liberal learning. They argue that programs of this kind advance liberal learning by cultivating skills required to engage the great questions of human flourishing, by fostering development of students' economic imagination and by enhancing students' ability to engage in genuine intellectual discovery. Details on the history and resource commitments for various program aspects are provided, allowing readers to identify program elements appropriate for replication at their home institutions.